Predictors of Extended Length of Hospital Stay in Adolescent Idiopathic Scoliosis Patients Undergoing Posterior Segmental Instrumented Fusion: An Analysis of 407 Surgeries Performed at a Large Academic Center. Issue 10 (15th May 2019) - Sultan, Assem A.; Berger, Ryan J.; Cantrell, William A.; Samuel, Linsen T.; Ramanathan, Deepak; Churchill, Jessica; Minkara, Anas A.; Golubovsky, Joshua; Bachour, Salam; Pasadyn, Selena; Karnuta, Jaret M.; Tamer, Pierre; et al.
Abstract : Study Design: Retrospective cohort study. Objective: The aims of this study were to (1) compare patient and procedure-specific characteristics among those who had short versus long hospital stays and (2) identify independent risk factors that may correlate with extended length of hospital stay (LOS) in patients with adolescent idiopathic scoliosis (AIS) who underwent posterior segmental instrumented fusion (PSIF). Summary of Background Data: Reducing the LOS and identifying risk factors associated with extended admission have become increasingly relevant to healthcare policy makers. There is currently limited research identifying risk factors that correlate with extended stay in patients undergoing PSIF for AIS. Methods: A single-institution, longitudinally maintained database was queried to identify 407 patients who met specific inclusion and exclusion criteria. Based on the distribution and median LOS in the cohort (4 days), patients were divided into those who had long versus short LOS. In both groups, patient demographics, comorbidities, preoperative scoliosis curve measurements, surgery-related characteristics, and complications were analyzed. A univariate and multivariate regression analysis was then conducted to identify independent risk factors associated with extended LOS. Results: Patients who had extended LOS tended to be women (84.6% vs. 75%, P  = 0.01), had more levels fused (9 ± 2 vs. 7 ± 2 levels, P  < 0.001), had more major postoperative complications (0.8% vs. 7.4%, P  = 0.002), had more blood loss during surgery (723 ± 548 vs. 488 ± 341 cm 3, P  < 0.001), and received less epidural analgesia for pain control (69% vs. 89%, P  < 0.001). Except for higher thoracic kyphosis, long LOS patients did not have worse preoperative radiographic curve parameters. Multivariate logistic analysis identified female sex, having ≥9 ± 2 levels of fusion, operative blood loss, major postoperative complications, lack of epidural analgesia, and higher thoracic kyphosis as independent risk factors correlating for extended LOS. Conclusion: Independent risk factors identified by this study may be used to recognize patients with AIS at risk of prolonged hospital stay. Level of Evidence: 3 Abstract : Identified independent risk factors for extended length of stay (LOS) in AIS patients undergoing PSIF. Factors were compared among patients who had long (n = 175) vs. short (n = 232) LOS. Postoperative major complications, operative blood loss, ≥9 ±2 fused levels, higher preoperative thoracic kyphosis, and lack of epidural analgesia were identified.